Next-Generation BIM Competency: Curriculum Integration to Equip UTM Civil Engineering Graduates for Industry Demands (International Journal of Built Environment and Sustainability, 2025)
Building Information Modelling has modernized the landscape of construction management and education by presenting innovative resources that enrich the teaching and application of industry-specific management practices. However, there remains a lack of standardised criteria for cultivating skilled BIM graduates and proving that current course information meets the construction industry's demands for fresh graduates. This study aims to integrate BIM into the civil engineering curriculum at Universiti Teknologi Malaysia (UTM) to better equip undergraduates with the competencies required by the Malaysian construction industry. Using a mixed-method explanatory sequential design, the study focuses on quantitative data collection and analysis, then transitions to qualitative methods to validate the initial findings and provide further insights. Data was collected from 90 civil engineering students at UTM who had completed BIM courses, with a response rate of 48.65%. The findings indicate that the current curriculum does not fully prepare graduates with the essential BIM skills required in the workplace, as BIM adoption in Malaysia is largely confined to 3D applications. The study identifies key technical skills for BIM-proficient graduates, such as modelling, information management, project coordination and interoperability with BIM tools. While non-technical skills go to adaptability and flexibility, continuous learning, collaboration and visualisation. To enhance the curriculum, it is recommended to provide elective courses in BIM, continuous curriculum updates, soft skills developments and hands-on experience. A BIM conceptual framework for integration into the UTM curriculum is proposed based on data collected from surveys, expert consultations, and an extensive literature review. The study presents valuable insights into the current state of BIM education at UTM and can be a point of reference for future research on standardising BIM teaching protocols in Higher Education Institutions (HEIs).
Keywords: Building Information Modelling, conceptual framework, civil engineering curriculum, improvements, UTM